Analysis The Social Community Reception “We Care Community” on The Television Show “Berbagi Rizki” On Net TV - Meydiana Rosha Riszkya (International Journal of Social Sciences Review, 2020)
Mass media such as television is an effective tool to influence how people think, one of the reason is because it’s familiarity and how easy to access it. Television can be found in almost all households. Therefore as a communication media, it has the ability to accessed public and personal spaces. Television is an advance technology, it delivers messages in audio-visual form. How audiences receive broadcasts from NET.TV which previously air program that is new and fresh, then makes a program called Berbagi Rizki, which adopts existing programs that glorifying poverty such as Bedah Rumah, Uang Kaget, Mikrofon Pelunas Hutang, Orang Pinggiran, and many others. This research uses a qualitative approach with data collection methods in the form of in-depth interviews, document study, and observation. The researcher uses the concept of cultural studies and uses the theory of reception analysis. The result of this study, indicate that the majority of interviewees with 4 peoples tend to be in the position of the meaning of the negotiations. The interviewees interpret by negotiating, which means that the audience could accept or not accept the meaning of the message for a specific reason. For some of the reasons, it found that the audience wants programs such as Berbagi Rizki to be present to have more long-term effects and be more creative in terms of packaging of the program without being exaggerated or subtracted.